2017
DOI: 10.3892/ijo.2017.4222
|View full text |Cite
|
Sign up to set email alerts
|

miR-135b-5p promotes gastric cancer progression by targeting CMTM3

Abstract: CKLF-like MARVEL transmembrane domain containing 3 (CMTM3) is considered to be a tumor suppressor gene in multiple types of malignancies. Previous studies have indicated that CMTM3 suppresses metastasis and epithelial-mesenchymal transition (EMT) in gastric cancer. However, its role in gastric cancer cell proliferation has rarely been discussed. Moreover, the regulatory mechanisms of CMTM3 in gastric cancer remain unclear. In this study, RT‑qPCR and IHC were used to assess the expression of CMTM3 and miR‑135b‑… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 37 publications
1
35
0
Order By: Relevance
“…In non-small cell lung cancer, amplification of miR-135b suppressed the chemoresistance of cancer cells to cisplatin treatment by downregulating Frizzled-1 (55). However, opposite effects of miR-135b-5p in certain cancers have also been reported (56,57). This could be partially explained by the mechanism by which miRNA binding to mRNAs is often achieved with imperfect complementarity, and its targets varied in different cellular contexts and tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…In non-small cell lung cancer, amplification of miR-135b suppressed the chemoresistance of cancer cells to cisplatin treatment by downregulating Frizzled-1 (55). However, opposite effects of miR-135b-5p in certain cancers have also been reported (56,57). This could be partially explained by the mechanism by which miRNA binding to mRNAs is often achieved with imperfect complementarity, and its targets varied in different cellular contexts and tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in human renal cell carcinoma (RCC), CMTM5 was significantly downregulated, and overexpression of CMTM5 efficiently suppressed the migration and invasion of RCC cells, and inhibited the cell growth of RCC cells by inducing cell cycle arrest at G0/G1 phase, which were indicated that CMTM5 functioned as a tumor suppressor in RCC cells . In gastric cancer, overexpression of CMTM3 suppressed cell proliferation, cell cycle progression and invasion, and promoted cell apoptosis, which also indicated that CMTM3 was a tumor suppressor gene in gastric cancer …”
Section: Discussionmentioning
confidence: 99%
“…18 In gastric cancer, overexpression of CMTM3 suppressed cell proliferation, cell cycle progression and invasion, and promoted cell apoptosis, which also indicated that CMTM3 was a tumor suppressor gene in gastric cancer. 22 CMTMs 6, 7, and 8 forms a gene cluster on 3p22, a chromosomal region rich in tumor-suppressor genes, whereas only CMTM7 has been shown to be downregulated or silenced in several malignancies, but its function and roles were still unknown in liver cancer. 5,10,23 Several studies have helped to elucidate the mechanisms of CMTM7 as a tumor suppressor, including those performed on EGFR internalization, AKT signaling pathway inhibition, and promoter methylation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some studies have suggested that miRNAs can function as important specific regulators in a number of biologic processes (7). The correlation between microRNA-135b (miR-135b) and the Laurén classification, tumor differentiation, invasion, and pathologic tumor-nodemetastasis stage of GC was outlined in a previous study (8). The overexpression of miR-135b has been found to be conducive to the chemoresistance of cells, while promoting the chemosensitivity of drug-resistant lung cancer cell lines (9).…”
mentioning
confidence: 99%